2022
DOI: 10.1186/s40634-022-00491-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic release of the pectoralis minor tendon from the coracoid for pectoralis minor syndrome

Abstract: Purpose The term “pectoralis minor syndrome” refers to this constellation of symptoms that can occur when the pectoralis minor (Pm) is shortened and contracted. Release of the tendon of the Pm from the coracoid has been reported to provide substantial clinical improvement to patients presenting with pectoralis minor syndrome. The purpose of this study was (1) to describe the technique for endoscopic release of pectoralis minor tendon at the subdeltoid space, (2) to classify the pectoralis minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…If patients fail this protocol, as in this case report, then surgical options are considered. Although traditionally open treatments focusing on first rib resection and scalenectomy were the standard of care 9,10 , many have started using minimally invasive approaches targeting the pectoralis minor and infraclavicular space 7,11 . As seen in this case, once the diagnosis of nTOS has been established, arthroscopic pectoralis minor release, suprascapular nerve release, and brachial plexus neurolysis combined with a 3-month dedicated scapular rehabilitation program (Appendix 2) can lead to marked improvements in shoulder pain, function, and patient-reported outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If patients fail this protocol, as in this case report, then surgical options are considered. Although traditionally open treatments focusing on first rib resection and scalenectomy were the standard of care 9,10 , many have started using minimally invasive approaches targeting the pectoralis minor and infraclavicular space 7,11 . As seen in this case, once the diagnosis of nTOS has been established, arthroscopic pectoralis minor release, suprascapular nerve release, and brachial plexus neurolysis combined with a 3-month dedicated scapular rehabilitation program (Appendix 2) can lead to marked improvements in shoulder pain, function, and patient-reported outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al 10 found variations in the complication rates between first rib resection and supraclavicular release without resection, reporting a 10% to 13% increase when rib resection was performed. Alternatively, isolated pectoralis minor release has been shown to have promising results when performed through open 6,[22][23][24] and arthroscopic techniques 7,11,25,26 . Furthermore, a comparative series suggested it to be superior when performed alone than in combination with first rib resection 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another international multicenter study demonstrated similarly good improvements without any major complications. 61 Ultimately, these data highlight the large variability in open treatment for NTOS, with overall unreliable outcomes compared to VTOS. The literature regarding arthroscopic management is currently modest but demonstrates initial promise as a relatively safe and reliable technique in treating this condition.…”
Section: Expected Outcomesmentioning
confidence: 95%